Application and Manual Encryption Process with The Combination Algorithm of One Time Padand Vigenere Cipher. (November 2020) - Siregar, Siti Julianita; Zarlis, Muhammad; Situmorang, Zakarias
Abstract: Cryptography is a branch of science which study art or a way to secure an information in order to that information becomesincomprehensible to third parties who does not have the authority. The intention of cryptography also serves as multiple aspects in information security such as confidentiality, data integrity, authentication, and non-repudiation. One of the things that be done to maintain the safety of information, is by encrypting the message to disguise the original message so that third parties will not be able decipher it in the event of an interception. Therefore, in order to secure the information, by encrypting the key using a different key technique is generally done with combining two algorithms which is One Time Pad with random key generator and Vigenere cipher using XOR and XNOR. The encryption process result from One Time Pad algorithm are cipherteks while theVigenere Cipher algorithm is the XOR cipherkey and XNOR cipherkey.